'We will build an over bridge': Gujarati Dalit poetry and the politics of cow protection. Issue 3 (3rd July 2018) - Jadeja, Gopika
Abstract : In 2015, many states in India banned the production and consumption of beef, with several states implementing stricter enforcement of already existing beef bans. The rhetoric of the bans evokes the protection of Hindu sensibilities, which consider the cow sacred. It has been observed that the political ascendency of the Bharatiya Janata Party and its ideology of Hindu Nationalism give impetus to the bans lending force to political and cultural organisations involved in cow vigilantism. This article explores the Hindu sense of disgust associated with professions related to the skinning and tanning of rawhide as well as the consumption of beef and carrion, which renders the untouchable body polluted, denying it personhood. Taking the Dalit protests following an assault on four Dalit youth in Mota Samadhiyala village of Gujarat on 11 July 2016, this article focuses on the Dalit response, both by activists and poets, to the proscription against beef. While Dalit activists have protested against assaults on those disposing of dead cattle, it is in poetry that the Dalit response to the disgust associated with the consumption of beef and carrion finds expression. Dalit poets bring the polluting body to the centre; claiming personhood and forging a new aesthetic.